Water for Domestic Ducks: The Benefits and Challenges in Commercial Production - Babington, Sarah; Campbell, Dana L. M. (Frontiers in Animal Science, 2022)
Although we have been farming ducks for at least 4,000 years, with some accounts suggesting domestication having begun more than 38,000 years ago, there are still many unknowns in how best to optimize domestic duck welfare in a commercial setting. Ducks being waterfowl, are semi-aquatic and have unique behavioral needs when compared to other commonly farmed poultry species. Providing ducks with open water which allows for full body immersion so that they may perform their full repertoire of water-related behaviors is important for their health and welfare. However, in a commercial setting this remains challenging due to biosecurity, contamination, health, and management concerns. An important question is therefore how best to provide ducks with a commercially feasible and safe water source in which they can derive maximum welfare and health benefits with no adverse consequences to health or global water resources. This review considers the amount of water provision necessary to satisfy duck’s water-related needs to enhance yet not compromise their welfare in a commercial setting based on current knowledge, as well as identifies the outstanding questions for future research to address.